Conducting psychological assessments : a guide for practitioners - Wright, A. Jordan (Hoboken, N.J. : Wiley, 2011)
"The major market need for this book comes from the fact that the bulk of the literature on psychological assessment focuses on individual tests, rather than the process of using tests as part of an overall integrative assessment process. The author has taught many Ph.D. students psychological assessment and supervised students taught by other professors, and it is clear to him that while interpretation of individual tests is relatively consistent, the basic foundations of how to use test data and how to integrate them into coherent and useful narratives varies greatly from assessor to assessor depending on their training. Many students and psychologists focus so much on adequate administration, scoring, and interpretation of individual tests that little attention is paid to the integration, conceptualization, and write-up phases of the process. This book provides concrete examples to illustrate how to navigate this process, which is too often left to chance."--
Machine generated contents note: Introduction. -- Chapter 1: Clinical Interviewing and Hypothesis Building. -- Chapter 2: Selecting Tests. -- Chapter 3: Testing. -- Chapter 4: Integrating Data. -- Chapter 5: Writing Reports. -- Chapter 6: Providing Feedback. -- Introduction to Part 2: Case Studies. -- Chapter 7: An Underachieving Woman: Lorraine Ryder. -- Chapter 8: A Recovering Alcoholic: Tati Roca. -- Chapter 9: A Young Man Who Steals: Daniel Delgado. -- Chapter 10: A Boy in Foster Care: Dashawn Terry. -- Chapter 11: An Anxious Girl: Heather Daltry. -- Chapter 12: An Aggressive Boy: Christopher Santiago. -- References.
Keywords: Psychodiagnostics